Between expertise and engagement: a qualitative study of Namibian geoscientists' views, attitudes, motivations, and objectives regarding public engagement with science - Josephine Naambo Uushona; Marina Joubert (Geoscience Communication, 2026)
Abstract. Geoscientists are increasingly expected to engage with society on issues such as mining, groundwater management, energy transitions, and environmental sustainability, yet public engagement in the geosciences remains limited. This is largely due to reliance on one-way communication models and the tendency for geoscientists to communicate primarily within their own discipline. Drawing on qualitative interviews with Namibian geoscientists from government, industry, and academia, this study examines how geoscientists understand public engagement, how they perceive public audiences, and what motivates or constrains their participation. The findings reveal a strong reliance on deficit-model assumptions, including the belief that public resistance to geoscientific issues stems mainly from a lack of knowledge and that education plays a central role in fostering public trust and support. While participants expressed positive attitudes toward public engagement and confidence in their communication abilities, engagement was largely framed as informing and educating rather than listening, collaboration, or shared knowledge production. Structural barriers, including limited institutional support, lack of training, time constraints, and minimal incentives, further restrict meaningful engagement. At the same time, the study identifies emerging recognition of the importance of trust-building, mutual learning, and community involvement, particularly in contexts affected by resource extraction. The study argues that strengthening the role of geoscience in Namibian society requires moving beyond deficit-based communication toward dialogic, context-sensitive, and participatory engagement approaches.